2018
DOI: 10.1126/sciadv.aau1338
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field multiphoton imaging through scattering media without correction

Abstract: Focusing ultrashort laser pulses in time in tandem with single-pixel detection images at depth with no sample characterization.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 63 publications
(84 reference statements)
1
42
0
Order By: Relevance
“…Rapid MPM may be enabled by the concept of temporal focusing (TF), where the axial localisation is performed by focusing a pulse in time rather than in space [8,9], alleviating the need for point-scanning with a facile use of a diffracting element. Recently, TF has come to the forefront with the realisation that spectrally dispersed light preserves spatial fidelity throughout scattering media due to the temporal pulse compression being supported only by the inphase, minimally scattered photons [10][11][12][13]. Wide-field TF MPM has been demonstrated as a novel option for correction-free imaging at a depth of up to seven scattering mean-free-path lengths with two-photon [10] excitation and may go further using three-photon [14] excitation modes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid MPM may be enabled by the concept of temporal focusing (TF), where the axial localisation is performed by focusing a pulse in time rather than in space [8,9], alleviating the need for point-scanning with a facile use of a diffracting element. Recently, TF has come to the forefront with the realisation that spectrally dispersed light preserves spatial fidelity throughout scattering media due to the temporal pulse compression being supported only by the inphase, minimally scattered photons [10][11][12][13]. Wide-field TF MPM has been demonstrated as a novel option for correction-free imaging at a depth of up to seven scattering mean-free-path lengths with two-photon [10] excitation and may go further using three-photon [14] excitation modes.…”
mentioning
confidence: 99%
“…Fig. 3 shows 4.8-µm beads imaged through a 360-µm thick scattering phantom (mean-free-path length, l s = 115 µm), described in [10]. At this thickness, multiple scattering of the two-photon signal scrambles spatial information such that no discernible image can be formed at the camera.…”
mentioning
confidence: 99%
“…These advantages have sparked recent interest by numerous groups to realize and apply single-pixel TFTP microscopy to image deep inside scattering media [13,14]. A key motivation behind using the single-pixel architecture is to achieve a large FOV, without significantly compromising the frame rate and image quality.…”
mentioning
confidence: 99%
“…However, it is important to point out that the frame rate of single-pixel cameras is set by the number of illumination patterns needed for the image acquisition and this is traditionally the Nyquist rate. For example, authors in [14] recently demonstrated a widefield TFTP microscope using a Hadamard basis scan. Considering a state-of-the-art pattern generator operating at 22 kHz, this scan will produce images with 128 × 128 pixels at ~1.3 frames per second.…”
mentioning
confidence: 99%
See 1 more Smart Citation